The Georgian Opera from the 1920s to the 1950s: A ‘Mega Weapon’ for the Soviet Union’s Ideology - Ghvinjilia Gvantsa (Musicology Today, 2024)
The paper discusses Georgian opera from the 1920s to the 1950s. It combined the function of mass culture, aiming to control citizens’ behavior and impact the masses in order to achieve socialist goals. The totalitarian regime strategically utilized the opera as a means of cultural expression to reinforce communist values. Soviet opera, including its Georgian variant, served as a tool for indoctrination, shaping public views in the desired way by the ruling party. The study aims to investigate the Georgian opera in the context of Soviet ideology. The research draws on interdisciplinary perspectives to explore the interplay between art and ideology. These goals imply studying the mechanism of the impact of ideology on art in general and determining the stylistic characteristics of Georgian opera. Analysis has been conducted in two phases: a) investigating the mechanism of the impact of Marxist-Leninist ideology on the society through art and the use of monumental genres such as the opera, large-scale sculptures and mosaic panels, for propaganda goals; b) a review of Georgian operas. Historical and comparative research methods are used in the article. In conclusion, it is emphasized that the opera perfectly corresponded to the goal of indoctrinating industrial workers, leaders, and the ‘New Soviet man’ in general. The criterion for evaluating Soviet opera, including the Georgian variant, was not its aesthetic value but its ‘ideological correctness’. The method of socialist realism, upon which Georgian opera was based, served as a means of disguising ideological goals, thus bringing the opera beyond the traditional aesthetic contexts of art music.